Knowledge and attitudes about essential newborn care in women experiencing motherhood for the first time - Gonzales López, Katherine Milagros; Bernedo-Moreira, David Hugo; Gonzales López, Jaime Natanael; Loayza-Apaza, Yesenia Tania; Pacompía Quispe, Héctor Fredy; Papanicolau Denegri, Jorge Nicolás Alejandro (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
For new mothers, the arrival of a newborn to the family is one of the most exciting and rewarding experiences. However, it can also cause moments of uncertainty and anxiety, especially with respect to the basic things to give to the newborn; in this context, the present study aims to determine whether the knowledge and attitudes about essential newborn care in women experiencing motherhood for the first time are different. For this purpose, a quantitative approach, non-experimental design, cross-sectional and correlational level was used; the instrument was a questionnaire, whose reliability index was a Cronbach's Alpha 0,891; the sample consisted of 200 primiparous mothers from a public health institution and 200 primiparous mothers from a private health institution, during the year 2022. The results show a high level of knowledge of 94 % in the public institution and 96 % in the private institution, and a high level of attitude of 70 % in the public hospital and 76 % in the private institution. At the inferential level, the Mann-Whitney U test (z=11492) and (p=0,582) indicate that there are statistically significant differences between the level of knowledge; on the other hand, (z=31037) and (p=0,894) show that there are no statistically significant differences in the level of attitude. It is concluded that the level of knowledge of the new mothers is different, however, the level of attitude is similar to that of the first mothers.